Stik Bawang Kombinasi Modified Cassava Flour, Isolated Soy Protein, Teri Medan, dan Guar Gum dengan Protein dan Kalsium sebagai Kudapan Alternatif bagi Anak Penyandang Autism: Garlic Stick with Modified Cassava Flour, Isolated Soy Protein, Medan Anchovy, and Guar Gum Containing Protein and Calcium as an Alternative Snack for Children with Autism - Aulia, Noni Angelina Tazky; Adi, Annis Catur (Amerta Nutrition, 2025)
Background: Sensitivity to gluten and casein in children with Autism Spectrum Disorder (ASD) is crucial to symptom severity, making their elimination necessary. However, the rising prevalence of ASD in Indonesia is not matched by the recommended dietary consumption. A garlic stick formulated with Modified Cassava Flour (MOCAF), Isolated Soy Protein (ISP), medan anchovy, and guar gum offers a gluten- and casein-free alternative while serving as a potential source of protein and calcium for ASD children aged 4-9 years. Objectives: To analyze the acceptability and nutrient content (protein and calcium) of garlic sticks made with MOCAF, ISP, medan anchovy, and guar gum. Methods: This research was a pure experimental study using a Completely Randomized Design (CRD) with four treatments. F0 (0% MOCAF, 0% ISP, 0% medan anchovy, 0% guar gum), F1 (51% MOCAF, 9% ISP, 2% medan anchovy, 1% guar gum), F2 (42% MOCAF, 16% ISP, 4% medan anchovy, 2% guar gum), and F3 (32% MOCAF, 23% ISP, 6% medan anchovy, 3% guar gum). Organoleptic values were analyzed using Kruskal-Wallis and Mann-Whitney U test. Protein and calcium levels were assessed using the Kjeldahl method and Atomic Absorption Spectroscopy. Results: F3 had the highest organoleptic acceptability. The protein and calcium content per 100 g of garlic stick were 8.26 g and 89.24 mg, respectively. A significant difference was observed between F0 and F3 flavor (p-value=0.004). Conclusions: F3 was the optimal formula. One serving (55 g) met 11-18% of the protein requirement, while two servings were necessary to fulfill the calcium requirement for a single snacking occasion.